When the Virtual World Becomes an Escape: The Link Between Loneliness and Problematic Internet Use Among Late Adolescents - Hamidah, Riska (Merpsy Journal, 2024)
Emerging from the digital landscape of Indonesia, late adolescents have emerged as the most frequent users of the internet. Nevertheless, several issues linked to internet usage can precipitate a maladaptive behavior called Problematic Internet Use (PIU). Individuals plagued by loneliness appear to be predisposed to engaging in excessive internet access. This study aims to investigate the role of loneliness in Problematic Internet Use among late adolescents. The total sample size for this research comprises 309 participants, selected via the accidental sampling method. The assessment tools employed include the UCLA Loneliness Scale Version 3 and the Generalized Problematic Internet Use Scale 2 (GPIUS2). Data analysis entails the application of a linear regression test using SPSS version 26. The findings reveal that loneliness exerts a substantial 19.9% influence on Problematic Internet Use among late adolescents in Jakarta. Internet usage activities are demographic factors that differentiate PIU among late adolescents. This study highlights the importance of involving adolescents in positive academic and social activities and the need for intervention for wise internet usage.